Innovation and Accountability in Teacher Education Setting Directions for New Cultures in Teacher Education - Wyatt-Smith, Claire; Adie, Lenore; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2018)
This is the foundational book for the new series, Teacher Education, Learning Innovation and Accountability. The book canvasses research, practice and policy perspectives in teacher education across diverse geographic, social and political contexts. It explores the lifespan of teacher development from initial preparation through to graduate classroom practice as it occurs in an intensifying culture of standards and regulation. The characterization of initial teacher education (ITE) in a crucible of change permeates throughout the book. The chapters open up new ways of thinking about innovation and accountability in ITE and the professionalization of teaching, exploring fundamental questions, such as (3z(BWho are the actors in teacher preparation and how do they interact? How can we learn about the quality of teacher education? Where can we hear the voices of teacher educators and preservice teachers, as well as school-based teacher educators? What are the new and emerging roles of others in teacher education who have not been involved previously, including employing authorities?(3y (B(p. 22). While the book provides responses to these and other provocative questions, it also offers new insights into innovative teacher education from a wide range of policy and practice contexts.s
1 Setting directions for new cultures in teacher education: The move to large scale collaborative professionalism -- Part I Accountability and change in teacher education -- 2 Accountability in teacher education in Norway: A case study of mistrust and trust -- 3 Notes from a small country: Teacher education, learning innovation and accountability in Scotland -- 4 Lost in transition: Learning to teach in the era of test based accountability -- 5 The explicit nature of educational goals for the 21st century -- 6 Challenges for initial teacher education in the context of "21st century" learning imperatives -- 7 Conceptions of readiness in initial teacher education: Quality, impact, standards and evidence in policy directives -- 8 Research-informed conceptualization and design principles of teacher performance assessments: Wrestling with system and site validity -- Part II Preparing teachers for diverse learners and context -- 9 Analyzing curriculum orientations of kindergarten curriculum -- 10 Engaging with ambivalence: The neglect of early childhood teacher education in initial teacher education reform in Australia -- 11 preparing teachers for assessment in schools: The influence of teacher educators -- 12 Looking for synergies to meet the challenges of teacher education -- 13 Enhancing inclusive education through teacher education reforms -- 14 Is quality initial teacher education where the music stops? Conceptualizing the becoming of a teacher: Lessons from the field -- Part III Partnerships and professional cultures -- 15 Early career teachers' perceptions of initial teacher education -- 16 Revisiting the teaching practicum: Effecting innovation or entrenching the status quo? Reflections from an ITE program in South Africa -- 17 School-based work in initial teacher education: Responding to policy in practice -- 18 Designing for integration in initial teacher education (ITE) curricula: The Hong Kong postgraduate diploma in education (PDGE) -- 19 Teacher education in a crucible of change.
Keywords: Schools; Teaching and Teacher Education; Professional & Vocational Education; Educational Policy and Politics; Schools and Schooling